DEVELOPMENT OF INNOVATION-INVESTMENT ACTIVITY OF ENTERPRISES IN RUSSIA: MAIN PROBLEMS AND TRENDS - O. Burova (Вестник университета, 2016)
The article deals with the main tendencies of innovative-investment activity development of Russian companies and the features and problems of reproduction of fixed assets.